2020
DOI: 10.1111/febs.15664
|View full text |Cite
|
Sign up to set email alerts
|

Functional reciprocity of proteins involved in mitosis and endocytosis

Abstract: Mitosis and endocytosis are two fundamental cellular processes essential for maintaining a eukaryotic life. Mitosis partitions duplicated chromatin enveloped in the nuclear membrane into two new cells, whereas endocytosis takes in extracellular substances through membrane invagination. These two processes are spatiotemporally separated and seemingly unrelated. However, recent studies have uncovered that endocytic proteins have moonlighting functions in mitosis, and mitotic complexes manifest additional roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 140 publications
0
4
1
Order By: Relevance
“…Different from the prevailing claims that pinocytosis is shut down during mitosis [41][42][43], we found here that macropinocytosis was decreased but not completely arrested in cell-cycle M-phase. Confocal microscopic examining the co-uptake of Tat/pGL3-Ca 2+ nanoparticles with Dextran in unperturbed cells showed that they were still internalized via macropinocytosis in different sub-phases of cell-cycle (Fig.…”
Section: Cell-cycle-dependent Macropinocytic Uptake Of Tat/ Pdna-ca 2...contrasting
confidence: 99%
“…Different from the prevailing claims that pinocytosis is shut down during mitosis [41][42][43], we found here that macropinocytosis was decreased but not completely arrested in cell-cycle M-phase. Confocal microscopic examining the co-uptake of Tat/pGL3-Ca 2+ nanoparticles with Dextran in unperturbed cells showed that they were still internalized via macropinocytosis in different sub-phases of cell-cycle (Fig.…”
Section: Cell-cycle-dependent Macropinocytic Uptake Of Tat/ Pdna-ca 2...contrasting
confidence: 99%
“…They can translate each other and participate in the tricarboxylic acid (TCA) cycle, the dysbiosis of which is associated with the pathogenesis and development of tumors [ 51 ]. Additionally, the decreased pathways in nucleotide excision repair (NER) and endocytosis in brain tumors insinuate a disruption in epigenetics and cellular processes [ 52 , 53 ]. NER is a key DNA repair mechanism that can remove helices distorting DNA adducts.…”
Section: Discussionmentioning
confidence: 99%
“…[b]: %M Removal percent of heavy metals. Zn 2 + , Ni 2 + , Mg 2 + , ect..) on the apatitic surface using ion exchange method constitutes the subject of several works [37,38,39] As mentioned respectively by M. Othmani et al [38] and L. Veselinovic et al, [39] the replacement rate of the calcium by copper is up to 15 % however, for the cobalt ion the substitution rate does not exceed 12 %. In accordance with our results, the calcium hydroxyapatite surface has mostly a greater affinity towards copper ion than cobalt.…”
Section: Effect Of Heavy Metal Naturementioning
confidence: 99%